Types of appropriation of folklorisms in the poem “Wrath of Poseidon” (Zien Journal of Social Sciences and Humanities, 2022)
In this paper, the types of appropriation of folklorisms in the poem “Wrath of Poseidon” by Karakalpak poet Ibrahim Yusupov are studied. First, a general description of the poem’s connection with folklore is given. Then, the simple and complex folklorisms found in the poem are analyzed. Also, the use of stylized folklorisms in the poem is deeply studied in the work